Biased behavior in borrowing from loan sharks - Novita Rahayu Pratiwi; Nur Khusniyah Indrawati; Risna Wijayanti (Jurnal Ekonomi & Keuangan Islam, 2023)
Purpose – This study aims to explore and understand how the mindset of merchant women in Montong Traditional Market so choose loan sharks as their loan source, which refers to the perspective of behavior and financial literacy.Methodology – This qualitative research with a Schutz phenomenological design, takes the research setting in Montong Traditional Market, Tuban. Data were collected through observation, interviews, and documentation.Findings – The results of the study show five biased of merchant women towards loan sharks, namely confirmation bias, framing, herding effect, hindsight bias, and representativeness. 'Agamis' in the merchant women in Montong Traditional Market does not guarantee that she is free from loan sharks. Implications – The results of this study indicate that related parties, such as religious leaders, the society leader, and cooperatives in Montong Traditional Market, Tuban, are expected to be able to increase education related to financial literacy through existing programs effectively and efficiently. Banks and cooperatives in the Montong Traditional Market area should be able to pick up the ball by providing door-to-door services to merchant women in Montong Traditional Market as a maximum effort to eradicate loan shark practices.Originality – This study explores the mindset of merchant women on loan sharks, whereas previous studies related to loan sharks have only explored them from an economic perspective.